Adverse events of local treatment in long-term head and neck rhabdomyosarcoma survivors after external beam radiotherapy or AMORE treatment. Issue 11 (July 2015) - Schoot, Reineke A.; Slater, Olga; Ronckers, Cécile M.; Zwinderman, Aeilko H.; Balm, Alfons J.M.; Hartley, Benjamin; van den Brekel, Michiel W.; Gupta, Sanjeev; Saeed, Peerooz; Gajdosova, Eva; Pieters, Bradley R.; Gaze, Mark N.; et al.
Abstract Background Radiotherapy is a well-known cause of adverse events (AEs). To reduce AEs, an innovative local treatment was developed in Amsterdam: Ablative surgery, MOuld brachytherapy and surgical REconstruction (AMORE). Aims: (1) to determine the prevalence of AEs in HNRMS survivors and (2) to compare AEs between survivors treated with the international standard: external beam radiotherapy (EBRT-based: London) and survivors treated with AMORE if feasible, otherwise EBRT (AMORE-based: Amsterdam). Methods All HNRMS survivors, treated in London or Amsterdam between January 1990 and December 2010 (n = 153), and alive ⩾2 years post-treatment were eligible (n = 113). A predefined list of AEs was assessed in a multidisciplinary clinic and graded according to the Common Terminology Criteria for Adverse Events. Results Eighty HNRMS survivors attended the clinic (median follow-up 10.5 years); 63% experienced ⩾1 severe or disabling event, and 76% had ⩾5 AEs (any grade). Survivors with EBRT-based treatment were, after adjustment for site, age at diagnosis, and follow-up duration, at increased risk to develop any grade 3/4 event or ⩾5 AEs (any grade) compared with survivors with AMORE-based treatments (p = 0.032 and 0.01, respectively). Five year overall survival (source population) after EBRT-based treatment was 75.0%, after AMORE-based treatment 76.9%, p = 0.56. Conclusion This study may serve as a baseline inventory and can be used in future studies for prospective assessments of AEs following the introduction of novel local treatment modalities. AMORE-based local treatment resulted in similar overall survival and a reduction of AEs secondary to local treatment.